2016
DOI: 10.1039/c6cp02446g
|View full text |Cite
|
Sign up to set email alerts
|

Probing the energy levels of perovskite solar cells via Kelvin probe and UV ambient pressure photoemission spectroscopy

Abstract: We present a study of the energy levels present in a perovskite solar cell using Kelvin probe and UV air photoemission measurements. By constructing a detailed map of the energy levels in the system we are able to predict the maximum open circuit voltage of the solar cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 35 publications
(36 reference statements)
6
105
1
2
Order By: Relevance
“…It can be used to study the electrical potential distribution across the internal interfaces of inorganic solar cell devices and P3HT:PCBM polymer solar cells . KPFM were also applied to PSCs for studying the local grain boundaries, the internal potential distribution, as well as the energy band diagram . More detailed descriptions of the working principle of KPFM can be found in literature .…”
Section: Methods For Deriving Elamentioning
confidence: 99%
“…It can be used to study the electrical potential distribution across the internal interfaces of inorganic solar cell devices and P3HT:PCBM polymer solar cells . KPFM were also applied to PSCs for studying the local grain boundaries, the internal potential distribution, as well as the energy band diagram . More detailed descriptions of the working principle of KPFM can be found in literature .…”
Section: Methods For Deriving Elamentioning
confidence: 99%
“…These factors include (i) dopant materials employed and its concentration, (ii) environmental conditions under which the film is prepared,[35e,f,58] (iii) chemical interactions with the underneath layer where spiro‐MeOTAD is deposited,[56c,59] (iv) diffusion and phase‐segregation phenomena of dopants in the HTM,[35e,f,42] (v) influence originated from the measurement conditions and techniques, e.g., cyclic voltammetry (CV) performed in electrolyte solution;[2a,60] ultraviolet photoelectron spectroscopy (UPS)[35f,58] performed under vacuum conditions; photoelectron spectroscopy in air (PESA). [60b,61] Fantacci et al employed density functional theory (DFT) calculations to show that increase in oxidized species of spiro‐MeOTAD + leads to a shift of HOMO towards E F . Schölin et al showed a similar effect of p‐doping with increased concentration of LiTFSI dopants, where the pristine spiro‐MeOTAD had a HOMO leading edge at ≈1 eV below E F .…”
Section: Spiro‐meotad Energy Levelsmentioning
confidence: 99%
“…We observe that the Fermi levels for the 15, 35, and 120 nm thick perovskite films deposited on PEDOT:PSS (5.02, 5.05, and 5.15 eV, respectively) were strongly influenced by the WF of the PEDOT:PSS (measured at 5.00 eV), i.e., the Fermi level of the perovskite was “pulled” toward that of PEDOT:PSS 40, 41. This implies that the depletion width of the perovskites on PEDOT:PSS extended through the bulk of the film 42.…”
mentioning
confidence: 94%